Peningkatan Aktivitas Antioksidan pada Ekstrak Daun Kelor (Moringa oleifera) melalui Fermentasi: Studi Perbandingan Kandungan Fenolik dan Aktivitas Antioksidan - Hery Muhamad Ansory; Nuraini Harmastuti; Windia Wulantika; Afif Meilana Sindani Putri (Fakultas Farmasi Universitas Setia Budi, 2023)
This study aimed to investigate the effect of fermentation on the antioxidant activity and phenolic content of 96% ethanol extract from Moringa oleifera leaves. While the antioxidant potential of Moringa leaves has been recognized, this research introduces a novel concept of utilizing fermentation to enhance the levels of active compounds. The state of the art in antioxidant activity and fermentation is used to validate the significant improvement in antioxidant activity. The findings provide new insights into utilizing Moringa leaves as a natural antioxidant source obtained through fermentation. The research methodology involved fermenting the 96% ethanol extract from Moringa leaves using Lactobacillus B bacteria for 24, 48, and 72 hours. The phenolic content was measured using the Folin-Ciocalteu method, while the antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results demonstrated a significant increase in phenolic content after the fermentation process. The phenolic content of the fermented Moringa leaf extract was 86.133±5.925 mgGAE/gram after 24 hours, increased to 91.244±7.374 mgGAE/gram at 48 hours, and reached 122.578±9.576 mgGAE/gram at 72 hours. Additionally, the antioxidant activity also increased with fermentation time. The IC50 values for samples fermented for 24, 48, and 72 hours were 60.887 µg/ml, 58.742 µg/ml, and 53.169 µg/ml, respectively. These results indicate that fermentation of Moringa leaf extract can significantly enhance phenolic content and antioxidant activity.